Design and implementation of a color QR code generator and reader for shopping mall navigation - Badawi, Bakri; Mohd Aris, Teh Noranis; Che Pa, Noraini (Little Lion Scientific, 2022)
In this paper, we proposed an indoor navigation system for navigation inside shopping malls or hypermarkets. the indoor navigation system provides an easy way to navigate to a product or store. The system consists of two parts. The first part is the encoder or the QR code generator which will be used by the shopping mall manager to generate QR codes. The generated QR code needs to be installed in the mall. The second part is the decoder which needs a mobile phone. The decoder will take the required destination from the shopper and then using the information stored inside the QR code will build the virtual map and provide the navigation instruction. The experiment was done by testing the encoder to generate QR codes for two different virtual buildings. While the decoder tested to get the location for multiple destinations.